From eco-sustainability to risk assessment of aquaculture products - Gandini, G; Ababouch, L; Anichini, L (Veterinary research communications, 2009)
The increasing demand for fishery products and the technical and commercial opportunities now available make the development of aquaculture an important subject for the policy of the fishery sector, in particular concerning aspects of its environmental and ecological sustainability. The latest studies show that it is possible to apply an ecological approach to the aquaculture sector and hence increase the interactions between fisheries and other activities such as fish/molluscs, fish/seaweed, rice-growing/fish. In this way we take part in the improvement of the environment thanks to the recycling of organic food, the reduction of pesticide use and the control of environmental euthrophication. In order to support and facilitate trade, but at the same time ensure the safety and quality of products, a harmonization of the policies for food safety protecting the products throughout the whole food chain is required (from the sea to the table). The above mentioned policy, based on scientific knowledge, relies on the analysis of risks from the competent Authorities and on the proper application of HACCP from the industries of the sector.